Emerging PEGylated non-biologic drugs. (3rd April 2019) - Park, Eun Ji; Choi, Jiyoung; Lee, Kang Choon; Na, Dong Hee
ABSTRACT: Introduction : PEGylation is a well-established technology for improving the therapeutic value of drugs by attaching polyethylene glycol (PEG). The first PEGylated enzyme products appeared on the market in the early 1990s; currently, more than 18 PEGylated products have been approved by Food and Drug Administration, which encompass various classes of drug molecules, such as enzymes, interferons, granulocyte colony-stimulating factors, hormones, antibody fragments, coagulation factors, oligonucleotide aptamers, synthetic peptides, and small organic molecules. Areas covered : While PEGylated products mainly comprise biologic drugs, such as recombinant proteins and enzymes, non-biologic drugs have recently emerged as a target for PEGylation. This review focuses on the recent development of PEGylated non-biologic drugs, such as small organic molecules, synthetic peptides, and aptamers. Expert opinion : Several PEGylated versions of anti-cancer drugs, opioid agonists, glucagon-like peptide-1 receptor agonists, and oligonucleotide aptamers are in active development stage, and it is likely that they will have a dramatic impact on the market. Although some safety concerns about PEG in clinical trials have been recently issued, PEGylation is still a commercially attractive proposition as a half-life extension technology for long-acting drug development. Trial registration: ClinicalTrials.gov identifier: NCT01492101. Trial registration: ClinicalTrials.gov identifier: NCT02367820. Trial registration: ClinicalTrials.gov identifier: NCT00520390. Trial registration: ClinicalTrials.gov identifier: NCT02119819. Trial registration: ClinicalTrials.gov identifier: NCT03520972. Trial registration: ClinicalTrials.gov identifier: NCT03604419. Trial registration: ClinicalTrials.gov identifier: NCT00804986. Trial registration: ClinicalTrials.gov identifier: NCT03672604. Trial registration: ClinicalTrials.gov identifier: NCT01089517. Trial registration: ClinicalTrials.gov identifier: NCT01944839. Trial registration: ClinicalTrials.gov identifier: NCT01940900. Trial registration: ClinicalTrials.gov identifier: NCT01940887. Trial registration: ClinicalTrials.gov identifier: NCT00932100. Trial registration: ClinicalTrials.gov identifier: NCT00715455. Trial registration: ClinicalTrials.gov identifier: NCT01872572. Trial registration: ClinicalTrials.gov identifier: NCT01848106. Trial registration: ClinicalTrials.gov identifier: NCT00432770. Trial registration: ClinicalTrials.gov identifier: NCT00632242. Trial registration: ClinicalTrials.gov identifier: NCT00742612. Trial registration: ClinicalTrials.gov identifier: NCT00507338. Trial registration: ClinicalTrials.gov identifier: NCT02397954. Trial registration: ClinicalTrials.gov identifier: NCT00976378. Trial registration: ClinicalTrials.gov identifier: NCT00976378. Trial registration: ClinicalTrials.gov identifier: NCT01486797. Trial registration: ClinicalTrials.gov identifier: NCT01521533. Trial registration: ClinicalTrials.gov identifier: NCT01085292. Trial registration: ClinicalTrials.gov identifier: NCT01547897. Trial registration: ClinicalTrials.gov identifier: NCT01372137. Trial registration: ClinicalTrials.gov identifier: NCT01691040. Trial registration: ClinicalTrials.gov identifier: NCT02079896.